Enhancing Customer Satisfaction in Commuter Rail Services through Multimodal Integration and Digital Payment Adoption: A Case Study in Greater Bandung - Euis Saribanon; Agus Nugroho; Siti Nurhayati; Novi Indah Susanthi; Devi Ratnasari (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study evaluates customer satisfaction with Commuter Line services in Area II of Bandung during the new normal era. The study focuses on multimodal transportation integration and digital payment system implementation. A survey was conducted with 616 respondents representing the various demographics of service users. The results of the analysis show that customers are highly satisfied with the provided services, especially regarding cleanliness, comfort, and digital accessibility. Technology application and improved accessibility have proven to be key factors in creating a positive travel experience. However, Importance Performance Analysis (IPA) results indicate that improvements to the bank transfer payment system are needed to meet customer expectations. These findings provide a foundation for developing adaptive, responsive, and inclusive strategies to improve the quality of public transportation services.